On new characters of the eggs of Embioptera with the description of a new species of Saussurembia (Anisembiidae). - Szumik, Claudia Adriana (2007)
Nine egg characters for eleven species of Embioptera are described for the first time. Egg variability indicates its potential use in taxonomy. Here, we analyse the correlation of this variability with the ordinal classification. In addition, a new species of Saussurembia (Anisembiidae) from Trinidad is described, including classical traits in the systematics of Embioptera (adult male and female), as well as general features of the egg and maternal behaviour.